Optical Scattering Properties of Intralipid Phantom in Presence of Encapsulated Microbubbles - Homa Assadi; Raffi Karshafian; Alexandre Douplik (International Journal of Photoenergy)
In imaging, contrast agents are utilized to enhance sensitivity and specificity of diagnostic modalities. In ultrasound imaging, microbubbles (MBs)—a gas-core shell-encapsulated agent—are used clinically as contrast agents. The working hypothesis of this study is that microbubbles can be employed as an intravascular contrast agent in optical imaging systems. In this work, the interaction of light and microbubbles in a turbid medium (intralipid) was investigated, particularly, the effect of MBs on the reduced scattering and absorption coefficients. Diffuse reflectance (DR) and total transmittance (TT) measurements of highly scattering intralipid suspension (0.5–5%) were measured using spectroscopic integrating sphere system in the absence and presence of Definity microbubbles. The optical properties were computed using the inverse adding doubling (IAD) software. The presence of microbubbles increased DR and decreased TT of intralipid phantoms. In the presence of MBs (0.5% volume concentration), the reflectance of the intralipid phantom increased from 35% to 100%. The reduced scattering coefficient increased significantly (30%) indicating potential use of MBs as optical contrast agents in light based modalities.